The role of internal feedback in the evolution of the dwarf spheroidal galaxy Leo II. Issue Volume 15:Issue S359(2020) (March 2019) - Hazenfratz, Roberto; Lanfranchi, Gustavo A.; Caproni, Anderson
Abstract: This work aims to explore the different processes of formation and evolution of dwarf spheroidal galaxies in the Local Group analyzing internal and external feedbacks, taking Leo II as a model of parametrization due to its adequate large distance to the Milky Way, in order to minimize potential external effects. We present a discussion of the first results regarding the processes of formation and galactic evolution from the gas hydrodynamics. Combined with previous studies for other similar systems, such results have the potential to establish strong links for the elaboration of a consistent and coherent scenario of formation and evolution of the dwarf spheroidal galaxies in the Local Group.